2016
DOI: 10.2166/ws.2016.050
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in groundwater under locations with high livestock density in Germany

Abstract: Antibiotics are deployed in large quantities both in human and in veterinary medicine. Studies show that antibiotic residues occur in the environment (e.g. soil and surface waters). In some cases they were also detected in ground and drinking water. However, the degree of groundwater pollution by antibiotic residues from livestock farming is unknown. Therefore, the federal environment agency (UBA) supported a project that aimed to investigate near-surface groundwater samples in regions of high livestock densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Recently, antibiotic presence in surface water and groundwater was reported in a drinking water production site, in Germany, and among 26 antibiotics, eight were detected in surface water, while in groundwater, only trimethoprim was detected with concentrations between 5 and 12 ng/L, among the 11 wells [28]. Another research group also carried out their work at the same region, in the high livestock production area and found sulfamethoxazole up to 950 ng/L, and sulfadiazine and sulfamethazine below 12 ng/L among seven wells [16,82].…”
Section: Detection Of Antibiotics In the Environmental Matricesmentioning
confidence: 97%
“…Recently, antibiotic presence in surface water and groundwater was reported in a drinking water production site, in Germany, and among 26 antibiotics, eight were detected in surface water, while in groundwater, only trimethoprim was detected with concentrations between 5 and 12 ng/L, among the 11 wells [28]. Another research group also carried out their work at the same region, in the high livestock production area and found sulfamethoxazole up to 950 ng/L, and sulfadiazine and sulfamethazine below 12 ng/L among seven wells [16,82].…”
Section: Detection Of Antibiotics In the Environmental Matricesmentioning
confidence: 97%
“…SDZ was detected in relatively high concentrations (except for in June), averaging 12 ng•L −1 in March and 21.3 ng•L −1 in August. 2016) reported that antibiotics entered surface waters through the effluents discharged from sewage treatment plants, sewage sludge, soil, groundwater, livestock excreta, and fertilizers containing livestock excreta; subsequently, pollutants from the surface water entered groundwater through the soil [42]. Accordingly, the observed concentrations and frequencies of antibiotics in the groundwater were lower than those in the surface water since the former could initially enter through other filtration and dilution media such as soils and streams.…”
Section: Groundwatermentioning
confidence: 99%
“…Between 50% and 90% of antibiotics used in humans and animals are excreted via urine and feces as a mixture of parent and metabolite form into the environment via waste streams or stormwater runoff [2,3]. As a result, antibiotics have been detected in all of environmental compartments, e.g., in groundwater [4], drinking water [5][6][7], wastewater [7], surface water [8][9][10], sediment [11][12][13], and sludge [12]. It is inevitable that aquatic organisms have the potential to be exposed to ecotoxic effects of these unexpected residual antibiotics through the food web beginning with first consumer, e.g., algae [13], which means it may threaten to the global public health and the ecological security.…”
Section: Introductionmentioning
confidence: 99%